2013
DOI: 10.1001/jamaophthalmol.2013.5521
|View full text |Cite
|
Sign up to set email alerts
|

Readability Assessment of Online Ophthalmic Patient Information

Abstract: IMPORTANCE Patients increasingly use the Internet to access information related to their disease, but poor health literacy is known to impact negatively on medical outcomes. Multiple agencies have recommended that patient-oriented literature be written at a fourth-to sixth-grade (9-12 years of age) reading level to assist understanding. The readability of online patient-oriented materials related to ophthalmic diagnoses is not yet known. OBJECTIVE To assess the readability of online literature specifically for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
102
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 18 publications
5
102
1
Order By: Relevance
“…To our knowledge, this is one of few studies to use these five readability assessment tools to assess the readability of online patient education information relating specifically to congestive heart failure. The readability of web-based literature has been assessed in many healthcare arenas such as colorectal surgery, ophthalmology, dermatology, nephrology, orthopedics, psychiatry, and endocrinology [5, 2227]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is one of few studies to use these five readability assessment tools to assess the readability of online patient education information relating specifically to congestive heart failure. The readability of web-based literature has been assessed in many healthcare arenas such as colorectal surgery, ophthalmology, dermatology, nephrology, orthopedics, psychiatry, and endocrinology [5, 2227]. …”
Section: Discussionmentioning
confidence: 99%
“…While having a nearly unlimited knowledge base can be empowering, the unfiltered nature of the Internet can result in patient misinformation and anxiety due to medical jargon and difficult readability of the patient education materials. Guidelines set forth by American Medical Association (AMA) and the US Department of Health and Human Services (USDHHS) dictate that patient reading material should be no higher than a fifth- or sixth-grade reading level in order to be more accessible and comprehensible to the general public [5]. …”
Section: Introductionmentioning
confidence: 99%
“…3,28 Our analysis of PEMs from major ophthalmologic association websites is consistent with previous studies of ophthalmology-related online PEMs that have shown that readability exceeds the reading level of the average American. 9,29,30 Analyses using the FKGL, SMOG, CLI, GFI, NDC, NFC, and FORCAST numerical scales showed that PEMs were written at mean grade ranges all greater than the American Medical Association-and National Institutes of Health-recommended fourth-to sixth-grade reading level. The FRE score corresponded to a difficult level to read.…”
Section: Discussionmentioning
confidence: 99%
“…9 None of the webpages examined had a readability score within any of the recommended guidelines. There were several limitations to that study, however.…”
mentioning
confidence: 98%
“…Using the Flesch-Kincaid Formulae is relatively easy and inexpensive -a fact that has made it and other readability formulae quite popular among health literacy scholars. It is not uncommon to read articles with methods that that amount to copying the text from a Web site, pasting it into Microsoft Word, and running spell checker to generate readability scores (e.g., Cochrane, Gregory, and Wilson 2012;Edmunds, Barry, and Denniston 2013;Grewal and Alagartnam 2013;Rhee et al 2013;Sanghvi et al 2012). Further quantitative or qualitative analysis is rare.…”
Section: Introductionmentioning
confidence: 99%